2002
DOI: 10.1007/s005340200107
|View full text |Cite
|
Sign up to set email alerts
|

Nonparasitic solitary huge liver cysts causing intracystic hemorrhage or obstructive jaundice

Abstract: We report two cases of a nonparasitic solitary huge liver cyst. The first case, that of a 42-year-old woman, was admitted with a chief complaint of upper abdominal pain. Computed tomography (CT) scans revealed a huge cyst, 10 cm in diameter, in segments 4 and 5 of the liver, and spontaneous rupture of the cyst with intracystic hemorrhage. Her general condition was improved by transcatheter arterial embolization (TAE). Percutaneous cystic needle aspiration cytological examination revealed no malignant cells, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 20 publications
0
34
0
2
Order By: Relevance
“…Generally the patients might have acute or chronic upper abdomen pain, but some patients have no symptoms [1][2][3][4] . Extra attention should be paid to patients whose symptoms are relative to the severe complications caused by the intracystic hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally the patients might have acute or chronic upper abdomen pain, but some patients have no symptoms [1][2][3][4] . Extra attention should be paid to patients whose symptoms are relative to the severe complications caused by the intracystic hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…For poorly conditioned patients, transcatheter arterial embolization, transhepatic cyst drainage, intracystic ethanol injection or noninvasive methods are indicated. These methods can obtain therapeutic effect in some patients, though the bleeding may recur afterwards [3][4][5]14,15] . Surgery should be performed for most well conditioned patients, especially those whose diagnosis does not preclude malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Park et al (16) reported that an elevated serum CA 19-9 level may not be helpful in the preoperative diagnosis of biliary cystic neoplasm. In other reports, elevated serum CA19-9 levels were observed in one patient with an infected simple hepatic cyst complicated by an intracystic hemorrhage (17) and also in another patient with a ruptured hepatic cyst (18). The serum and cystic fluid CEA levels were similar in both entities (15).…”
Section: Discussionmentioning
confidence: 79%
“…When present, symptoms include fullness or upper abdominal mass, nausea, and occasional vomiting. Jaundice is an infrequent symptom [3,5,6]. Rapid enlargement of the cyst presenting as acute abdomen has been reported in some English publications [7].…”
Section: Discussionmentioning
confidence: 97%